Graham Bartram, Sarah McGaughey, and Galin Tihanov, editors. A Companion to the Works of Hermann Broch. Camden House, 2019. - Orel Beilinson (Studies in 20th & 21st Century Literature, 2022)
Review of Graham Bartram, Sarah McGaughey, and Galin Tihanov, editors. A Companion to the Works of Hermann Broch. Camden House, 2019. xii + 278 pp.
Keywords: Hermann Broch; New Objectivity; Vienna Circle